The Effectiveness of Cooperative Learning Using Vocabulary Flashcards on Students’ Mastery of English Adjectives - Ni Wayan Peni; Ni Luh Sutjiati Beratha; I Nyoman Suparwa (International Journal of Multilingual Education and Applied Linguistics, 2026)
This article investigates the effectiveness of cooperative learning using vocabulary flashcards in improving students’ mastery of English adjectives. The research was conducted due to students’ limited vocabulary knowledge. The objective of this article was to examine whether the implementation of a cooperative learning model supported by vocabulary flashcards could enhance students’ adjective mastery and learning engagement. A pre-experimental research design with a one-group pretest–posttest approach was employed. The participants consisted of 15 junior high school students enrolled in an English course. Data were collected through pretest, posttest, classroom observation, and a student response questionnaire. Quantitative data were analyzed using descriptive statistics and N-Gain analysis, while qualitative data were obtained from observation sheets and questionnaire responses. The findings indicate a noticeable improvement in students’ posttest scores compared to their pretest results, with the mean N-Gain score categorized as moderately effective. In addition, observation data revealed high levels of student participation during cooperative learning activities. Questionnaire results further showed positive student responses toward the use of cooperative learning and vocabulary flashcards, particularly in terms of motivation, confidence, and ease of understanding English adjectives. These findings suggest that cooperative learning combined with vocabulary flashcards can effectively support students’ vocabulary development and active engagement. In conclusion, the study provides empirical evidence that cooperative learning facilitates meaningful interaction and knowledge construction, supporting its implementation in English vocabulary instruction. However, future research is recommended to involve larger samples and comparative research designs to strengthen the generalizability of the findings.